Peran Kepala Desa Terhadap Pembangunan di Desa Wates Kecamatan Jenangan Kabupaten Ponorogo (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2021)
This study aims to determine the role of the village government in the development of the agricultural sector in Wates Village, Jenangan District, Ponorogo Regency. The type of research is qualitative with a descriptive approach. The research location is in Wates Village, Jenangan District, Ponorogo Regency. The key informants in this study were the Head of Wates Village and representatives of the Wates Village Farmer Group Association (Gapoktan). The research instrument consisted of interview guidelines, field observation notes, and documentation. From the research results, it is known that the Head of Wates Village has a very significant role in agricultural development in Wates Village, which is shown by: 1) Head of Wates Village is able to provide direction to subordinates in implementing development, 2) Head of Wates Village is able to make decisions in the process of implementing development, 3 ) Head of Wates Village is able to coordinate the implementation of village development; 4) Head of Wates Village is able to supervise activities in the process of implementing village government